A wizard of earthsea eaudiobook - Le Guin, Ursula K. (Earthsea, 2010)
In print for more than three decades and translated into dozens of languages, here is the audio release of the first book in The Earthsea Trilogy. This is a tale of wizards, dragons, and shadows, played in an archipelago of imagined islands. The young boy Sparrowhawk becomes apprentice to a Master Wizard; but impatience to learn faster takes him far from home to Roke Island, where he enters the School for Wizards. As a student of magic, Sparrowhawk exceeds his years in accomplishment, but pride and jealousy drive the boy to try certain dangerous powers too soon. A terrible evil is let loose in the land.